Resilience quantification model for cyber‐physical power systems - Mohammad AlMuhaini (IET Cyber-Physical Systems)
Abstract As power grids develop, their structure becomes more complex, multi‐dimensional, and digitalised—hence, it is referred to as cyber‐physical infrastructure. The sensitivity of grids to extreme cyber and physical events is becoming a hot research topic due to the increasing rate of such events and their catastrophic consequences. To produce accurate and comprehensive measures, modelling and assessing the resilience of power systems must include both the physical and cyber domains. However, resilience quantification models that include both domains have not received sufficient attention. A novel resilience model and quantification framework are proposed. The model is based on a resilience trapezoid that depicts the different phases of the cyber and physical domains during severe natural or anthropogenic events. A resilience index is also proposed to measure the resilience levels of local nodes and entire systems, including various factors that contribute to the modelled degradation states. Severe weather conditions were modelled to examine the impact of this category of events on the proposed resilience model.